Development and Regional Stability in Africa
XIX, 323 p. 5 illus., 4 illus. in color.
Keywords: This book critically engages with the development-security nexus in contemporary Africa, coinciding with the twentieth anniversary of the African Union (AU). Despite widespread discourse on the 'Africa Rising' narrative, many African states grapple with persistent economic challenges, violent conflicts, Afrophobia, and democratic setbacks. The AU's efforts, alongside those of other regional actors, to leverage regionalism for driving socio-economic and political development while ensuring peace and security have yielded limited results. Consequently, this edited volume takes an incisive approach to unpack the complex and vexed issues obstructing sustainable advancements in security and development in Africa. While existing studies have predominantly centered on conventional conflict and development concerns, this book sheds light on the emerging realities and evolving dynamics shaping the region's trajectory. Utilising a comprehensive case study approach, the book places Africa's challenges within both historical and contemporary contexts, aiming to present sustainable policy options to bridge the myriad gaps in the continent's peace, security, and governance architecture. By addressing the intricacies of balancing individual state interests with collective regional advancement, this volume offers a pathway toward unlocking Africa's potential for development and fostering a prosperous and harmonious 'Africa We Want'. Adeoye O. Akinola is Head of Research and Teaching, and African Union Studies at the Institute for Pan-African Thought and Conversation (IPATC), University of Johannesburg in South Africa. He obtained a doctorate from the University of KwaZulu-Natal, South Africa. He specialises in African political economy, African Union Studies, migration, conflict, and peace studies. Among his recent book publications are Contemporary Issues on Governance, Conflict and Security in Africa (Palgrave, 2023), and Worlds Apart? Perspectives of Africa-EU Migration (Jacana Media, 2022). Emmaculate Asige Liaga is a Postdoctoral researcher at the IPATC, University of Johannesburg in South Africa. She obtained a doctorate from the University of Pretoria, South Africa. Her research investigates the strategies of peacebuilding employed by both local and international organizations of peace operations in post-conflict communities, analysing the top-down and bottom-up approaches by both foreign intervention and local-level organizations.